The level of awareness on ASB2 unit trust among Generation Y / Sakinah Ishak and Norliana Juhari - Ishak, Sakinah; Juhari, Norliana (2014)
This research explores about the new product of ASNB which is Amanah Saham Berhad 2 (ASB2). The main purpose of this research was to identify the level of awareness on ASB2 unit trust amon g Generation Y. This research applied cross sectional studies where data collected by using questionnaire. The questionnaire consist questions regarding awareness, knowledge, social influence, marketing strategy and characteristics of funds. 150 respondents were selected among Generation Y in Kuala Lumpur. The result shows that there were three independent variables which are knowledge, marketing strategy and characteristics of funds are significant towards dependent variables. Meanwhile social influence were found to be insignificant with negative relationship towards the level of awareness on ASB2 unit trust among Generation Y. in addition, marketing strategy was found to be the most influence factor for the dependent variable based on regression analysis. Thus, marketing strategy such as advertising, promotion, or events should be implemented in order to improve the level of awareness among Generation Y. For future research, the number of respondent should be increase and the area of research can be extended to other places in order to obtain better result and generalizability.